Solid gel electrolyte, preparation method and application
The fluorine-containing inorganic solid gel electrolyte prepared by mixing inorganic porous fluoride with liquid electrolytes has been solved, and the safety and capacity attenuation problems of lithium metal batteries due to liquid electrolytes are achieved, and high lithium ion conductivity and high temperature stability are achieved. Improved the performance of lithium metal batteries.
Patent Information
- Application Number
- CN202411432954.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-02-14
AI Technical Summary
Due to the limitations of traditional liquid electrolytes, lithium metal batteries have safety problems such as leakage and combustion, and the decomposition of electrolytes leads to attenuation of battery capacity, affecting their commercial development.
A fluorine-containing inorganic solid gel electrolyte is prepared by mixing inorganic porous fluoride with liquid electrolyte. It has high lithium ion conductivity and high temperature stability, can effectively inhibit the growth of lithium dendrites, and form a stable solid electrolyte on the surface of lithium metal. Interface mask.
It significantly improves the circulation performance and high temperature performance of lithium metal batteries, reduces liquid content, improves safety, and is suitable for commercial applications of lithium metal batteries.
Smart Images

Figure BDA0005084228000000091 
Figure BDA0005084228000000101 
Figure BDA0005084228000000121
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium batteries, and in particular to a solid gel electrolyte, a preparation method and an application thereof. Background Art
[0002] To meet the growing demand for electric vehicles, grid-level energy storage and portable electronic devices, the development of a new generation of energy storage technology is urgent. The theoretical energy density of lithium metal batteries is as high as 2600Wh kg -1 , is the most promising alternative to commercial lithium-ion batteries. However, limited by traditional liquid electrolytes, lithium metal batteries face safety issues such as leakage and combustion, and continuous electrolyte decomposition also causes the battery capacity to decay continuously. Therefore, people have paid great attention to solid electrolytes, which avoid the use of volatile organic solvents and are expected to fundamentally eliminate the safety hazards brought by liquid electrolytes. Despite this, solid electrolytes still have defects such as low room temperature ionic conductivity and high solid-solid interface resistance, which seriously limit their commercial development.
[0003] The gel electrolyte obtained by compounding liquid electrolyte with solid polymer electrolyte can obtain high ionic conductivity, sufficient interface contact and good processability, and is one of the most promising electrolyte systems. However, the development of gel electrolytes with stable solid electrolyte interfaces and the ability to inhibit current collector corrosion is still under exploration. In addition, due to the presence of a large amount of organic solvents, gel electrolytes still face the problems of leakage and aggravated interface side reactions at high temperatures, which hinders the application of batteries under high temperature conditions. Summary of the invention
[0004] In order to overcome the defects of the prior art, one of the purposes of the present application is to provide a fluorine-containing inorganic solid gel electrolyte; the electrolyte is prepared by mixing inorganic porous fluoride and liquid electrolyte, has the characteristics of high lithium ion conductivity and good high-temperature stability, and can effectively inhibit the growth of lithium dendrites; the electrolyte effectively reduces the liquid content and has high safety; the electrolyte is suitable for lithium metal batteries, and the application of inorganic fluoride in the electrolyte can form a stable solid electrolyte interface film on the surface of lithium metal, and the cycle performance and high-temperature performance of the lithium metal battery of the electrolyte are significantly improved.
[0005] The technical solution of this application is as follows:
[0006] 1. A solid gel electrolyte, wherein the electrolyte comprises a metal fluoride, a lithium salt and an organic solvent;
[0007] The specific surface area of the metal fluoride is greater than or equal to 100 m 2 / g, preferably 100 to 300 m 2 / g, and / or, the pore size distribution range of the metal fluoride is 5nm to 10nm.
[0008] 2. The solid gel electrolyte according to item 1, wherein the metal fluoride is an alkaline metal fluoride, an alkaline earth metal fluoride or a Group III metal fluoride;
[0009] Preferably, the metal fluoride is selected from one or more of calcium fluoride, aluminum fluoride, barium fluoride, chromium fluoride, magnesium fluoride, sodium fluoride, potassium fluoride, lithium fluoride and cesium fluoride;
[0010] Further preferably, the metal fluoride is selected from one or more of calcium fluoride, aluminum fluoride, magnesium fluoride, barium fluoride and chromium fluoride.
[0011] 3. The solid gel electrolyte according to item 1, wherein
[0012] The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide.
[0013] 4. The solid gel electrolyte according to item 1, wherein
[0014] The organic solvent is selected from one or more of ethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dioxolane, butyrolactone, valerolactone, ethylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, succinonitrile, cyclopentane, fluoroethylene carbonate, bisfluoroethylene carbonate, ethyl trifluoropropionate, vinylene carbonate and vinyl ethylene carbonate.
[0015] 5. The solid gel electrolyte according to item 1, wherein
[0016] The mass ratio of the metal fluoride, the lithium salt and the organic solvent is 100:(10-40):(10-40).
[0017] 6. The solid gel electrolyte according to item 1, wherein
[0018] The preparation method of the metal fluoride is as follows:
[0019] Dissolve one or more of water-soluble boric acid, tungstic acid or silicic acid and metal nitrate in water, then add inorganic alkaline substances to precipitate metal and non-metal elements in the form of hydroxides, adjust the pH value to 7-8, age, filter and dry to obtain dried hydroxides;
[0020] The dried hydroxide is loaded into a steel tube, the temperature is raised, and nitrogen and anhydrous hydrogen fluoride are introduced at a volume ratio of 1: (0.1-10) for 2-10 hours; nitrogen and anhydrous hydrogen fluoride are introduced at a volume ratio of 1: (0.1-10) for 2-10 hours; nitrogen and anhydrous hydrogen fluoride are introduced at a volume ratio of 1: (0.1-10) for 2-10 hours; nitrogen and anhydrous hydrogen fluoride are introduced at a volume ratio of 1: (0.1-10) for 2-10 hours;
[0021] By purging with inert gas and cooling, metal fluorides can be obtained.
[0022] 7. A method for preparing a solid gel electrolyte as described in any one of items 1 to 6, comprising the following steps:
[0023] Under an inert gas, the lithium salt and the organic solvent are mixed and stirred to obtain a solution;
[0024] Under an inert gas, the solution and the metal fluoride are mixed and ground to obtain a solid gel electrolyte.
[0025] 8. The preparation method according to item 7, wherein the inert gas is nitrogen, argon or an argon-hydrogen mixed gas.
[0026] 9. Use of the solid gel electrolyte described in any one of items 1 to 6 or the solid gel electrolyte prepared by the method described in item 7 or 8 in the preparation of lithium batteries.
[0027] 10. A lithium battery comprising the solid gel electrolyte described in any one of items 1 to 6 or the solid gel electrolyte prepared by the method described in item 7 or 8.
[0028] This application has the following beneficial technical effects:
[0029] The electrolyte of the present application is prepared by mixing an inorganic porous fluoride with a liquid electrolyte, which achieves high ionic conductivity while effectively reducing the content of volatile organic solvents, has the characteristics of high lithium ion conductivity and good high-temperature stability, and can effectively inhibit the growth of lithium dendrites; the electrolyte effectively reduces the liquid content and has high safety; the electrolyte is suitable for lithium metal batteries, and the use of inorganic fluorides in the electrolyte can form a stable solid electrolyte interface film on the surface of lithium metal, and the cycle performance and high-temperature performance of the lithium metal battery of the electrolyte are significantly improved.
[0030] The present application provides a method for preparing a solid gel electrolyte. The preparation method has a simple process, cheap and readily available raw materials, is safe and pollution-free, and is suitable for large-scale batch production.
[0031] The present application provides a lithium metal battery, the electrolyte of the lithium metal battery is a fluorine-containing inorganic solid gel electrolyte described in the present application, and the cycle performance and high temperature performance of the lithium metal battery are significantly improved.
[0032] The present application provides a fluorine-containing inorganic solid gel electrolyte and a preparation method thereof. The electrolyte is prepared by mixing an inorganic porous metal fluoride with a liquid electrolyte, has the characteristics of high lithium ion conductivity and good high-temperature stability, and can effectively inhibit the growth of lithium dendrites; the electrolyte effectively reduces the liquid content and has high safety; the electrolyte is suitable for lithium metal batteries, and the use of inorganic porous metal fluorides in the electrolyte can form a stable solid electrolyte interface film (Solid Electrolyte Interface) on the surface of lithium metal, so that the cycle performance and high-temperature performance of the lithium metal battery are significantly improved; through the selection of liquid electrolyte, the electrolyte is suitable for lithium metal batteries and can match lithium iron phosphate (LFP) and high-voltage positive electrodes, such as LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811). The electrolyte preparation method has a simple process, the raw materials are cheap and readily available, and it is safe and pollution-free, and is suitable for large-scale batch production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a physical picture of the solid gel electrolyte prepared in Example 1.
[0034] Figure 2 : is the electrochemical impedance spectrum of the solid gel electrolyte prepared in Example 1.
[0035] Figure 3 This is the electrochemical window diagram of the solid gel electrolyte prepared in Example 1.
[0036] Figure 4 This is a graph of the 1C charge and discharge cycle performance of the LFP / Li battery assembled with the solid gel electrolyte prepared in Example 1 at room temperature.
[0037] Figure 5 This is a 1C charge and discharge cycle performance diagram of the LFP / Li battery assembled with the solid gel electrolyte prepared in Example 1 at 100°C.
[0038] Figure 6 This is a 0.5C charge and discharge cycle performance diagram of the NCM811 / Li battery assembled with the solid gel electrolyte prepared in Example 16 at room temperature. DETAILED DESCRIPTION
[0039] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the implementation of the present application, but the description is based on the general principles of the specification and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the attached claims.
[0040] The present application provides a solid gel electrolyte, wherein the electrolyte comprises a metal fluoride, a lithium salt and an organic solvent; the specific surface area of the metal fluoride is greater than or equal to 100 m 2 / g, preferably 100 to 300 m 2 / g, and / or, the pore size distribution range of the metal fluoride is 5nm to 10nm.
[0041] Specific surface area refers to the total area per unit mass of material, and the unit is m 2 / g. It is usually used to describe the surface characteristics of solid materials such as powders, fibers, and particles. The specific surface area of metal fluorides refers to the total area per unit mass of metal fluorides, and is usually measured by volume adsorption. Specifically, the nitrogen adsorption method is used to measure the specific surface area: the specific surface area is calculated by measuring the amount of nitrogen adsorbed in the pores.
[0042] Pore size distribution refers to the percentage of pores in a material calculated by number or volume. The pore size distribution of metal fluorides refers to the size of the pores in porous metal fluorides, usually measured by the BET method. Specifically, the characterization method is to characterize the pore size distribution of the material through a curve of the volume of each pore size and the corresponding partial pressure, which is an extension of the nitrogen adsorption method for determining specific surface area.
[0043] The applicant has found that only when the specific surface area of the metal fluoride or the pore size distribution range of the metal fluoride meets certain conditions, can a stable solid electrolyte interface film (Solid Electrolyte Interface) be formed on the lithium metal surface, so that the cycle performance and high temperature performance of the lithium metal battery are significantly improved, such as high room temperature ionic conductivity, small interface impedance, low average capacity decay after 1000 IC cycles at room temperature, and low average capacity decay after 200 IC cycles at 100°C.
[0044] In some specific embodiments of the present application, the specific surface area of the metal fluoride is greater than or equal to 100 m 2 / g, preferably 100 to 300 m 2 / g, for example, it can be 100m 2 / g, 110m 2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m 2 / g, 160m 2 / g, 170m 2 / g, 180m 2 / g, 190m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g, 230m 2 / g, 240m 2 / g, 250m 2 / g, 260m 2 / g, 270m 2 / g, 280m 2 / g、300m 2 / g or a range therebetween.
[0045] In some specific embodiments of the present application, the pore size distribution range of the metal fluoride is 5 nm to 10 nm.
[0046] In some specific embodiments of the present application, the metal fluoride is an alkaline metal fluoride, an alkaline earth metal fluoride or a Group III metal fluoride.
[0047] In some specific embodiments of the present application, the metal fluoride is selected from one or more of calcium fluoride, aluminum fluoride, barium fluoride, chromium fluoride, magnesium fluoride, sodium fluoride, potassium fluoride, lithium fluoride and cesium fluoride.
[0048] In some specific embodiments of the present application, the metal fluoride is selected from one or more of calcium fluoride, aluminum fluoride, magnesium fluoride, barium fluoride, and chromium fluoride.
[0049] In some specific embodiments of the present application, the metal fluoride is selected from one or more of calcium fluoride, aluminum fluoride, magnesium fluoride, barium fluoride, and chromium fluoride.
[0050] In some specific embodiments of the present application, the present application does not impose any limitation on the lithium salt, as long as the technical purpose is met, the lithium salt can be a common type in the art. For example, the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium difluorooxalatoborate (LiDFOB), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium bisfluorosulfonyl imide (LiFSI) and lithium (fluorosulfonyl) (trifluoromethanesulfonyl) imide (LiFTFSI).
[0051] In some specific embodiments of the present application, the present application does not make any limitation to the organic solvent, as long as the technical purpose is met, the organic solvent can be a common type in the art. For example, the organic solvent is selected from one or more of ethylene glycol dimethyl ether (DME), tetraethylene glycol dimethyl ether (TEGDME), dioxolane (DOL), butyrolactone (BL), valerolactone (VL), ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), succinonitrile (SN), cyclopentane (SL), fluoroethylene carbonate (FEC), bisfluoroethylene carbonate (DFEC), ethyl trifluoropropionate (FEP), vinylene carbonate (VC) and vinyl ethylene carbonate (VEC).
[0052] In some specific embodiments of the present application, the mass ratio of the metal fluoride, the lithium salt and the organic solvent is 100:(10-40):(10-40). For example, the mass ratio of the metal fluoride, the lithium salt and the organic solvent is 100:10:10, 100:10:20, 100:10:30, 100:10:40, 100:20:10, 100:20:20, 100:20:30, 100:20:40, 100:30:10, 100:30:20, 100:30:30, 100:30:40, 100:40:10, 100:40:20, 100:40:30, 100:40:40 or any range therebetween.
[0053] In some specific embodiments of the present application, the preparation method of metal fluoride is as follows: dissolve one or more of water-soluble boric acid, tungstic acid or silicic acid, and metal nitrate in water, then add inorganic alkaline substance, precipitate metal and non-metal elements in the form of hydroxide, adjust the pH value to 7-8, age, filter, and dry to obtain dried hydroxide; fill the dried hydroxide into a steel pipe, heat it, and pass nitrogen and anhydrous hydrogen fluoride at a volume ratio of 1: (0.1-10) for 2-10 hours; pass nitrogen and anhydrous hydrogen fluoride at a volume ratio of 1: (0.1-10) for 2-10 hours; pass nitrogen and anhydrous hydrogen fluoride at a volume ratio of 1: (0.1-10) for 2-10 hours; pass nitrogen and anhydrous hydrogen fluoride at a volume ratio of 1: (0.1-10) for 2-10 hours; purge with inert gas and cool it down to obtain metal fluoride.
[0054] In some specific embodiments of the present application, the preparation method of the metal fluoride is as follows: dissolving one or more of water-soluble boric acid, tungstic acid or silicic acid and metal nitrate in water to prepare a soluble salt solution; adding an inorganic base under stirring at 20°C to 60°C to precipitate the metal and non-metal elements in the form of hydroxides, adjusting the pH value to 7-8 and aging at 20°C to 80°C; filtering the precipitate and drying it to constant weight at 120°C; filling the dried hydroxide into an Inconel or monel steel pipe, heating it to 200°C, and introducing nitrogen and anhydrous hydrogen fluoride at a volume ratio of 2 / 1 for 4 hours; introducing nitrogen and anhydrous hydrogen fluoride at a volume ratio of 1 / 1 for 4 hours; introducing nitrogen and anhydrous hydrogen fluoride at a volume ratio of 1 / 2 for 4 hours; stopping the introduction of anhydrous hydrogen fluoride, purging with nitrogen and cooling to room temperature to obtain a porous metal fluoride.
[0055] The present application provides a method for preparing a solid gel electrolyte, which comprises the following steps: mixing the lithium salt and the organic solvent under an inert gas, stirring them uniformly to obtain a solution; and mixing the solution and the metal fluoride under an inert gas, grinding them to obtain a solid gel electrolyte.
[0056] In some specific embodiments of the present application, the inert gas is nitrogen, argon, or an argon-hydrogen mixed gas.
[0057] The present application provides the use of the above-mentioned solid gel electrolyte or the solid gel electrolyte prepared by the above-mentioned method in the preparation of a lithium battery.
[0058] In a specific embodiment of the present application, the method for preparing a lithium battery is as follows:
[0059] (1) Preparation of LFP positive electrode sheet:
[0060] Dissolve polyvinylidene fluoride (PVDF) in N-methylpyrrolidone to obtain a PVDF binder solution with a mass fraction of 5wt%; stir LFP, PVDF binder and conductive carbon black in a mass ratio of 8:1:1 to obtain a uniform positive electrode slurry; evenly coat the positive electrode slurry on a carbon-coated aluminum foil with a scraper, place it in a vacuum drying oven at 110°C and dry it for 12 hours, and cut it into discs with a diameter of 12mm for standby use after drying.
[0061] (2) Preparation of solid gel electrolyte:
[0062] In a glove box filled with argon (oxygen and water content are both less than 0.5ppm), lithium salt is dissolved in an organic solvent and stirred at room temperature to obtain a transparent solution. The above solution is mixed with metal fluoride (wherein the mass of the solution is 10wt% of the total mass of the electrolyte), and fully ground at room temperature to obtain a state gel electrolyte.
[0063] (3) Preparation of lithium metal batteries:
[0064] In a glove box filled with argon (oxygen and water content are both less than 0.5ppm), a small amount of fluorine-containing inorganic solid gel electrolyte is coated on the surface of the positive electrode (LFP positive electrode sheet) of the lithium metal battery, and the button battery is assembled in the order of the positive electrode sheet coated with electrolyte, the lithium metal negative electrode, the gasket, and the shrapnel.
[0065] In a specific embodiment of the present application, the method for preparing a lithium battery is as follows:
[0066] (1) Preparation of NCM811 positive electrode sheet:
[0067] Dissolve polyvinylidene fluoride (PVDF) in N-methylpyrrolidone to obtain a PVDF binder solution with a mass fraction of 5wt%; stir NCM811, PVDF binder and conductive carbon black in a mass ratio of 8:1:1 to obtain a uniform positive electrode slurry; evenly coat the positive electrode slurry on a carbon-coated aluminum foil with a scraper, place it in a vacuum drying oven at 110°C and dry it for 12 hours, and then cut it into discs with a diameter of 12mm for standby use.
[0068] (2) Preparation of fluorine-containing inorganic solid gel electrolyte:
[0069] In a glove box filled with argon (oxygen and water content are both less than 0.5ppm), lithium salt is dissolved in 1mL of organic solvent and stirred at room temperature to obtain a transparent solution. The above solution is mixed with calcium fluoride (wherein the mass of the solution is 10wt% of the total mass of the electrolyte), and fully ground at room temperature to obtain a fluorine-containing inorganic solid gel electrolyte.
[0070] (3) Preparation of lithium metal batteries:
[0071] In a glove box filled with argon (oxygen and water content are both less than 0.5 ppm), a small amount of fluorine-containing inorganic solid gel electrolyte is coated on the surface of the positive electrode (NCM811 positive electrode sheet) of the lithium metal battery, and the button battery is assembled in the order of the positive electrode sheet coated with electrolyte, the lithium metal negative electrode, the gasket, and the shrapnel.
[0072] The present application provides a lithium battery, which includes the above-mentioned solid gel electrolyte or the solid gel electrolyte prepared by the above-mentioned method.
[0073] When the specific surface area of metal fluoride is 100~300m 2 / g, and / or, when the pore size distribution range of the metal fluoride is 5nm to 10nm, the use of this inorganic porous metal fluoride in the electrolyte can form a stable solid electrolyte interface film (Solid Electrolyte Interface) on the surface of lithium metal, so that the cycle performance and high temperature performance of lithium metal batteries are significantly improved, such as high room temperature ion conductivity, small interface impedance, low average capacity decay of 1000 cycles of IC at room temperature, low average capacity decay of 200 cycles of IC at 100°C, or low average capacity decay of 200 cycles of 0.5C at room temperature. While effectively reducing the content of volatile organic solvents, high ionic conductivity is achieved, with the characteristics of high lithium ion conductivity and good high temperature stability, which can effectively inhibit the growth of lithium dendrites.
[0074] Preparation Example
[0075] Preparation Example 1
[0076] 42.6g of calcium nitrate and 0.16g of silicic acid are dissolved in water to prepare a water-soluble salt solution; 10% ammonia water is added under stirring at 40°C to precipitate calcium element in the form of hydroxide, and the pH value is adjusted to 7-8 and then aged at 30°C for 12h; the precipitate is filtered and dried at 120°C to constant weight; the dried hydroxide is filled into an Inconel or monel steel pipe, the temperature is raised to 200°C, nitrogen and anhydrous hydrogen fluoride are introduced at a volume ratio of 2:1, and maintained for 4h; nitrogen and anhydrous hydrogen fluoride are introduced at a volume ratio of 1:1, and maintained for 4h; nitrogen and anhydrous hydrogen fluoride are introduced at a volume ratio of 1:2, and maintained for 4h; the introduction of anhydrous hydrogen fluoride is stopped, purged with nitrogen and cooled to room temperature, and porous calcium fluoride can be obtained.
[0077] The specific surface area of porous calcium fluoride calculated by nitrogen adsorption method is 200m 2 / g, and the pore size distribution range is determined to be 5nm to 10nm through the curve diagram of the volume of each pore size and the corresponding partial pressure.
[0078] Preparation Example 2
[0079] Porous aluminum fluoride was synthesized by using 51.1 g of aluminum nitrate and 0.15 g of silicic acid and the rest of the process was as per Preparation Example 1.
[0080] Preparation Example 3
[0081] Porous barium fluoride was synthesized by using 28.7 g of barium nitrate and 0.07 g of silicic acid and the rest of the process was as per Preparation Example 1.
[0082] Preparation Example 4
[0083] Porous magnesium fluoride was synthesized by using 47.4 g of magnesium nitrate and 0.2 g of silicic acid and referring to Preparation Example 1 for the rest of the process.
[0084] Preparation Example 5
[0085] Porous chromium fluoride was synthesized by using 42.8 g of chromium nitrate and 0.11 g of silicic acid and the rest of the process was as per Preparation Example 1.
[0086] Preparation Example 6
[0087] Porous calcium fluoride was synthesized by using 42.6 g of calcium nitrate and 0.65 g of tungstic acid and referring to Preparation Example 1 for the rest of the process.
[0088] Preparation Example 7
[0089] 42.6 g of calcium nitrate and 0.2 g of boric acid were used, and the remaining steps were the same as in Preparation Example 1 to synthesize porous calcium fluoride.
[0090] Preparation Example 8
[0091] The precipitation reaction temperature was adjusted to 50°C, and the rest of the process was referred to Preparation Example 1 to synthesize porous calcium fluoride.
[0092] Preparation Example 9
[0093] The precipitation reaction temperature was adjusted to 60°C, and the rest of the process was carried out in accordance with Preparation Example 1 to synthesize porous calcium fluoride.
[0094] Preparation Example 10
[0095] The precipitation reaction temperature was adjusted to 30°C, and the rest of the process was referred to Preparation Example 1 to synthesize porous calcium fluoride.
[0096] Preparation Example 11
[0097] The aging temperature was adjusted to 20°C, and the rest of the process was referred to Preparation Example 1 to synthesize porous calcium fluoride.
[0098] Preparation Example 12
[0099] The aging temperature was adjusted to 40° C., and the rest of the process was referred to Preparation Example 1 to synthesize porous calcium fluoride.
[0100] Preparation Example 13
[0101] The aging temperature was adjusted to 50° C., and the rest was referred to Preparation Example 1 to synthesize porous calcium fluoride. The specific surface area and pore size distribution range were measured using the method in Preparation Example 1. The results are shown in Table 1.
[0102] Table 1
[0103]
[0104]
[0105] Example
[0106] 1. Electrochemical impedance spectroscopy (EIS) test: The test system was assembled into a Li / the electrolyte / Li symmetrical battery, and an AC impedance test was performed using a CHI660E electrochemical workstation from Shanghai Chenhua Instrument Co., Ltd. The test conditions were as follows: the test voltage was 0 V, the test frequency range was 0.1 Hz-1 MHz, and the test amplitude was 5 mV.
[0107] 2. Electrochemical window test: The test system was assembled into stainless steel (SS) / the electrolyte / Li battery, and a linear sweep voltammetry (LSV) test was performed using a CHI660E electrochemical workstation from Shanghai Chenhua Instrument Co., Ltd. The test conditions were as follows: voltage range 0-6V, scan rate 0.1mV / s.
[0108] 3. Electrochemical cycle test: The test system was assembled into lithium iron phosphate (LFP) / the electrolyte / Li battery, and the LAND battery test system of Wuhan Landian Electronics Co., Ltd. was used to perform charge and discharge cycles on the battery to be tested. The test conditions were as follows: the charge and discharge voltage range was 2.5-3.8V, and the cycle was performed at 1C.
[0109] 4. All batteries involved were assembled in a glove box filled with argon gas, where the oxygen and water content were less than 0.5 ppm.
[0110] Embodiment 1:
[0111] (1) Preparation of LFP positive electrode sheet:
[0112] Dissolve polyvinylidene fluoride (PVDF) in N-methylpyrrolidone to obtain a PVDF binder solution with a mass fraction of 5wt%; stir LFP, PVDF binder and conductive carbon black in a mass ratio of 8:1:1 to obtain a uniform positive electrode slurry; evenly coat the positive electrode slurry on a carbon-coated aluminum foil with a scraper, place it in a vacuum drying oven at 110°C and dry it for 12 hours, and cut it into discs with a diameter of 12mm for standby use after drying.
[0113] (2) Preparation of solid gel electrolyte:
[0114] In a glove box filled with argon (oxygen and water content are less than 0.5ppm), 0.144g of lithium salt (LiDFOB) was dissolved in 1mL of organic solvent (TEGDME), and stirred at room temperature to obtain a transparent solution. The above solution was mixed with calcium fluoride (wherein the mass of the solution was 10wt% of the total mass of the electrolyte), wherein the specific surface area of calcium fluoride was 200m 2 / g, the pore size distribution range of calcium fluoride is 5nm ~ 10nm, and it is fully ground and uniformly at room temperature to obtain a state gel electrolyte.
[0115] (3) Preparation of lithium metal batteries:
[0116] In a glove box filled with argon (oxygen and water content are both less than 0.5ppm), a small amount of fluorine-containing inorganic solid gel electrolyte is coated on the surface of the positive electrode (LFP positive electrode sheet) of the lithium metal battery, and the button battery is assembled in the order of the positive electrode sheet coated with electrolyte, the lithium metal negative electrode, the gasket, and the shrapnel.
[0117] The fluorine-containing inorganic solid gel electrolyte prepared in Example 1 was observed and tested as follows:
[0118] (1) Figure 1 The fluorine-containing inorganic solid gel electrolyte prepared in step (2) is translucent, and the liquid component and the solid component are evenly mixed without obvious fluidity.
[0119] (2) The room temperature electrochemical impedance spectroscopy of the fluorine-containing inorganic solid gel electrolyte prepared in Example 1 is shown in Figure 2 , it can be seen that the room temperature ionic conductivity of this fluorinated inorganic solid gel electrolyte (thickness 200 μm) is 0.29 mS cm -1 , can be cycled at room temperature, and the interfacial impedance of the lithium symmetric battery assembled with this electrolyte is only 38.8Ω, indicating that this fluorine-containing inorganic solid gel electrolyte has good compatibility with lithium metal.
[0120] (3) The electrochemical window test results of the fluorine-containing inorganic solid gel electrolyte prepared in Example 1 are shown in Figure 3 It can be seen that the electrochemical window of this fluorine-containing inorganic solid gel electrolyte reaches 5.26V, and it has good anti-oxidation stability.
[0121] (4) The battery charge and discharge cycle test of the LFP / Li battery assembled with the fluorine-containing inorganic solid gel electrolyte prepared in Example 1 at room temperature shows Figure 4 After 1000 cycles at 1C, the capacity is as high as 106.9 mAh g -1 The average capacity decay per cycle is only 0.024%, indicating that this fluorine-containing inorganic solid gel electrolyte improves the cycle performance of lithium metal batteries.
[0122] (5) The battery charge and discharge cycle test of the LFP / Li battery assembled with the fluorine-containing inorganic solid gel electrolyte prepared in Example 1 at high temperature (100° C.) shows Figure 5 After 200 cycles at 1C, the capacity is as high as 106.8 mAh g -1 The average capacity decay per cycle is only 0.093%, indicating that this fluorine-containing inorganic solid gel electrolyte improves the high-temperature performance of lithium metal batteries.
[0123] The difference between Examples 2 to 15 is only in Table 2, and the rest is the same as Example 1. The difference between Comparative Examples 1 to 2 and Example 1 is that no calcium fluoride is added in Comparative Example 1, and commercially available calcium fluoride is added in Comparative Example 2. The specific surface area of calcium fluoride in Comparative Example 2 is 0.78 m 2 / g, and the pore size distribution range is 5-30nm.
[0124] The testing methods of Examples 1 to 15 and Comparative Examples 1 to 2 are the same as those of Example 1. The results are shown in Table 4.
[0125] Table 2
[0126]
[0127] Embodiment 16:
[0128] (1) Preparation of NCM811 positive electrode sheet:
[0129] Dissolve polyvinylidene fluoride (PVDF) in N-methylpyrrolidone to obtain a PVDF binder solution with a mass fraction of 5wt%; stir NCM811, PVDF binder and conductive carbon black in a mass ratio of 8:1:1 to obtain a uniform positive electrode slurry; evenly coat the positive electrode slurry on a carbon-coated aluminum foil with a scraper, place it in a vacuum drying oven at 110°C and dry it for 12 hours, and then cut it into discs with a diameter of 12mm for standby use.
[0130] (2) Preparation of fluorine-containing inorganic solid gel electrolyte:
[0131] In a glove box filled with argon (oxygen and water content are less than 0.5ppm), 0.287g of lithium salt (LiTFSI) was dissolved in 1mL of organic solvent (FEP), and stirred at room temperature to obtain a transparent solution. The above solution was mixed with calcium fluoride (wherein the mass of the solution was 10wt% of the total mass of the electrolyte), wherein the specific surface area of calcium fluoride was 200m 2 / g, the pore size distribution range of calcium fluoride is 5nm-10nm, and it is fully ground and uniformly at room temperature to obtain a fluorine-containing inorganic solid gel electrolyte.
[0132] (3) Preparation of lithium metal batteries:
[0133] In a glove box filled with argon (oxygen and water content are both less than 0.5 ppm), a small amount of fluorine-containing inorganic solid gel electrolyte is coated on the surface of the positive electrode (NCM811 positive electrode sheet) of the lithium metal battery, and the button battery is assembled in the order of the positive electrode sheet coated with electrolyte, the lithium metal negative electrode, the gasket, and the shrapnel.
[0134] The inorganic solid gel electrolyte prepared in Example 16 was observed and tested as follows:
[0135] (1) The room temperature ionic conductivity of the fluorinated inorganic solid gel electrolyte prepared in Example 16 is 0.33 mS cm -1 , can be cycled at room temperature, and the interfacial impedance of the lithium symmetric battery assembled with this electrolyte is only 44.3Ω, indicating that this fluorine-containing inorganic solid gel electrolyte has good compatibility with lithium metal.
[0136] (2) The electrochemical window of the fluorine-containing inorganic solid gel electrolyte prepared in Example 16 is 5.51 V, and it has good anti-oxidation stability.
[0137] (3) The battery charge and discharge cycle test of the NCM811 / Li battery assembled with the fluorine-containing inorganic solid gel electrolyte prepared in Example 16 at room temperature is shown in FIG. Figure 6 After 200 cycles at 0.5C, the capacity is as high as 131.36 mAh g -1 The average capacity decay per cycle is only 0.119%, indicating that this fluorine-containing inorganic solid gel electrolyte improves the cycle performance of high-voltage lithium metal batteries.
[0138] The difference between Examples 17 to 19 is only in Table 3, and the rest is the same as Example 16. The difference between Comparative Examples 3 to 4 and Example 16 is that no calcium fluoride is added in Comparative Example 3, and commercially available calcium fluoride is added in Comparative Example 4. The specific surface area of calcium fluoride in Comparative Example 4 is 0.78 m 2 / g, and the pore size distribution range is 5-30nm. The testing methods of Examples 16-19 and Comparative Examples 3-4 are the same as those of Example 16, and the results are shown in Table 5.
[0139] Table 3
[0140]
[0141]
[0142] Table 4
[0143]
[0144] When the specific surface area of metal fluoride is 100~300m 2 / g, and / or, when the pore size distribution range of the metal fluoride is 5nm to 10nm, the use of this inorganic porous metal fluoride in the electrolyte can form a stable solid electrolyte interface film (Solid Electrolyte Interface) on the surface of lithium metal, so that the cycle performance and high temperature performance of lithium metal batteries are significantly improved, such as high room temperature ion conductivity, small interface impedance, low average capacity decay of 1000 cycles of IC cycle at room temperature, and low average capacity decay of 200 cycles of IC cycle at 100°C. While effectively reducing the content of volatile organic solvents, high ionic conductivity is achieved, with the characteristics of high lithium ion conductivity and good high temperature stability, which can effectively inhibit the growth of lithium dendrites.
[0145] Table 5
[0146]
[0147] When the specific surface area of metal fluoride is 100~300m 2 / g, and / or, when the pore size distribution range of the metal fluoride is 5nm to 10nm, the use of this inorganic porous metal fluoride in the electrolyte can form a stable solid electrolyte interface film (Solid Electrolyte Interface) on the surface of lithium metal, so that the cycle performance and high temperature performance of the lithium metal battery are significantly improved, such as high room temperature ionic conductivity, small interface impedance, and low average capacity decay after 200 cycles at 0.5C at room temperature. At this time, high ionic conductivity is achieved while effectively reducing the content of volatile organic solvents. It has the characteristics of high lithium ion conductivity and good high temperature stability, and can effectively inhibit the growth of lithium dendrites.
Claims
1. A solid gel electrolyte, wherein: The electrolyte comprises metal fluoride, lithium salt and organic solvent; The specific surface area of the metal fluoride is greater than or equal to 100 m 2 / g, preferably 100 to 300 m 2 / g, and / or, the pore size distribution range of the metal fluoride is 5nm to 10nm.
2. The solid gel electrolyte according to claim 1, wherein The metal fluoride is an alkaline metal fluoride, an alkaline earth metal fluoride or a Group III metal fluoride; Preferably, the metal fluoride is selected from one or more of calcium fluoride, aluminum fluoride, barium fluoride, chromium fluoride, magnesium fluoride, sodium fluoride, potassium fluoride, lithium fluoride and cesium fluoride; Further preferably, the metal fluoride is selected from one or more of calcium fluoride, aluminum fluoride, magnesium fluoride, barium fluoride and chromium fluoride.
3. The solid gel electrolyte according to claim 1, wherein The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium (fluorosulfonyl)(trifluoromethanesulfonyl)imide.
4. The solid gel electrolyte according to claim 1, wherein The organic solvent is selected from one or more of ethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, dioxolane, butyrolactone, valerolactone, ethylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, succinonitrile, cyclopentane, fluoroethylene carbonate, bisfluoroethylene carbonate, ethyl trifluoropropionate, vinylene carbonate and vinyl ethylene carbonate.
5. The solid gel electrolyte according to claim 1, wherein The mass ratio of the metal fluoride, the lithium salt and the organic solvent is 100:(10-40):(10-40).
6. The solid gel electrolyte according to claim 1, wherein The preparation method of the metal fluoride is as follows: Dissolve one or more of water-soluble boric acid, tungstic acid or silicic acid and metal nitrate in water, then add inorganic alkaline substances to precipitate metal and non-metal elements in the form of hydroxides, adjust the pH value to 7-8, age, filter and dry to obtain dried hydroxides; The dried hydroxide is loaded into a steel tube, the temperature is raised, and nitrogen and anhydrous hydrogen fluoride are introduced at a volume ratio of 1: (0.1-10) for 2-10 hours; nitrogen and anhydrous hydrogen fluoride are introduced at a volume ratio of 1: (0.1-10) for 2-10 hours; nitrogen and anhydrous hydrogen fluoride are introduced at a volume ratio of 1: (0.1-10) for 2-10 hours; nitrogen and anhydrous hydrogen fluoride are introduced at a volume ratio of 1: (0.1-10) for 2-10 hours; By purging with inert gas and cooling, metal fluorides can be obtained.
7. A method for preparing a solid gel electrolyte according to any one of claims 1 to 6, comprising the following steps: Under an inert gas, the lithium salt and the organic solvent are mixed and stirred to obtain a solution; Under an inert gas, the solution and the metal fluoride are mixed and ground to obtain a solid gel electrolyte.
8. The preparation method according to claim 7, wherein: The inert gas is nitrogen, argon or an argon-hydrogen mixed gas.
9. Use of the solid gel electrolyte according to any one of claims 1 to 6 or the solid gel electrolyte prepared by the method according to claim 7 or 8 in preparing a lithium battery.
10. A lithium battery comprising the solid gel electrolyte according to any one of claims 1 to 6 or the solid gel electrolyte prepared by the method according to claim 7 or 8.